Publishing Scholarly Articles: From Manuscript to Publication - Noori, Abdullah (Journal of Social Sciences - Kabul University, 2024)
Publishing in prestigious peer-reviewed academic journals is a pivotal pursuit for researchers and scholars, yet writing, submitting, and publishing a manuscript can be complicated and demanding. This study endeavors to guide researchers through transforming a conceptual manuscript into a successfully published work. It draws upon a thorough synthesis of existing literature and insights from experts to illuminate a holistic perspective on critical aspects, including effective manuscript preparation, journal selection, rigorous peer-review gauntlet, upholding ethical imperatives, and skillfully managing the post-submission process. Furthermore, the study offers strategies for amplifying the resonance of published research articles through various channels, such as social media, academic conferences, and institutional repositories. By elucidating the complexities inherent in academic publishing, this study stands as an indispensable beacon for researchers seeking to elevate the impact and visibility of their scholarly endeavors.